Effect of diurnal temperature range on the outpatient visits for acute bronchitis in children: a time-series study in Hefei, China. (March 2017) - Xie, M.-y.; Ni, H.; Zhao, D.-s.; Cheng, J.; Wen, L.-y.; Li, K.-s.; Yang, H.-h.; Wang, S.-s.; Zhang, H.; Wang, X.; Su, H.
Abstract: Objectives: To determine the relationship between diurnal temperature range (DTR) and outpatient visits for childhood acute bronchitis (AB) in Hefei, China, to analyze whether DTR effect was delayed, and to explore the susceptible populations. Study design: An ecological study. Methods: A Poisson generalized linear regression model combined with a distributed lag non-linear model was used to analyze the relationship between DTR and childhood AB from Hefei, China during 2010–2013, after adjusting for long-term trend and seasonality, mean temperature and relative humidity. Results: An adverse effect of DTR on childhood AB was observed, and the impact of DTR was greatest at three days lag, with a 1.0% (95% confidence interval = 0.5–1.6%) increase of AB cases per 1 °C increment of DTR. Female children and children aged 0–4 years appeared to be more vulnerable to DTR effect than other children. Conclusions: Our study suggests that large DTR may increase the incidence of childhood AB in Hefei, particularly for those who are female and young. Caregivers and health practitioners should be made aware of the potential threat posed by large DTR. Highlights: Time-series analysis was conducted to quantify the impacts of DTR on childhood AB. The risk of childhood AB increased significantly when DTR was above 10.9 °C. In our study, female children and children aged 0–4 years appeared to be more sensitive to DTR effect than other children. This study showed that the greatest effect of DTR on childhood AB was not acute, but occurred three days later.